A data-driven, meaningful, easy to interpret, standardised accelerometer outcome variable for global surveillance. Issue 10 (October 2019) - Rowlands, Alex V.; Sherar, Lauren B.; Fairclough, Stuart J.; Yates, Tom; Edwardson, Charlotte L.; Harrington, Deirdre M.; Davies, Melanie J.; Munir, Fehmidah; Khunti, Kamlesh; Stiles, Victoria H.
Abstract: Objectives: Our aim is to demonstrate how a data-driven accelerometer metric, the acceleration above which a person's most active minutes are accumulated, can (a) quantify the prevalence of meeting current physical activity guidelines for global surveillance and (b) moving forward, could inform accelerometer-driven physical activity guidelines. Unlike cut-point methods, the metric is population-independent (e.g. age) and potentially comparable across datasets. Design: Cross-sectional, secondary data analysis. Methods: Analyses were carried out on five datasets using wrist-worn accelerometers: children (N = 145), adolescent girls (N = 1669), office workers (N = 114), pre- (N = 1218) and post- (N = 1316) menopausal women, and adults with type 2 diabetes (N = 475). Open-source software (GGIR) was used to generate the magnitude of acceleration above which a person's most active 60, 30 and 2 min are accumulated: M60ACC ; M30ACC and M2ACC, respectively. Results: The proportion of participants with M60ACC (children) and M30ACC (adults) values higher than accelerations representative of brisk walking (i.e., moderate-to-vigorous physical activity) ranged from 17 to 68% in children and 15 to 81% in adults, tending to decline with age. The proportion of pre-and post-menopausal women with M2ACC values meeting thresholds for bone health ranged from 6 to 13%. Conclusions: These metrics can be used for global surveillance of physical activity, including assessing prevalence of meeting current physical activity guidelines. As accelerometer and corresponding health data accumulate it will be possible to interpret the metrics relative to age- and sex- specific norms and derive evidence-based physical activity guidelines directly from accelerometer data for use in future global surveillance. This is where the potential advantages of these metrics lie.